PATIENT SATISFACTION WITH INTEGRATED HIV AND ANTENATAL CARE SERVICES IN RURAL KENYA - Vo, Baotran N. (2012)
A cluster randomized controlled trial was initiated in Kenya to determine if full integration (FI) of HIV care, including HAART, into antenatal care (ANC) clinics improves health outcomes among HIV-infected women and exposed infants, compared to a non-integrated (NI) model. This paper examines ANC clients’ satisfaction with and preferences regarding HIV-integrated services. In this cross-sectional study, pregnant women attending five FI clinics (n=185) and four NI clinics (n=141) completed an interviewer-administered questionnaire following an ANC visit. By self-report, 55 women (17%) were HIV(+), 230 (71%) were HIV(−) and 40 (12%) did not know their HIV status. Among HIV-infected women, 79% attending FI clinics were very satisfied with their clinic visit compared to 54% of women attending NI clinics (P=0.044); no such difference was found among HIV-uninfected women. In multivariate analysis, overall satisfaction was also independently associated with satisfaction with administrative staff, satisfaction with health care providers, positive evaluation of wait time, and having encountered a receptionist. Full integration of HIV care into antenatal clinics can significantly increase overall satisfaction with care for HIV-infected women, with no significant decrease in satisfaction for HIV-uninfected women served in the same clinics.